Pengaruh Entrepreneurship Education Terhadap Entrepreneurial Intention Melalui Entrepreneurial Motivation Sebagai Mediasi Pada Mahasiswa Perguruan Tinggi Swasta Di Surabaya - Ratih Indriyani (Universitas Negeri Surabaya, 2017)
Entrepreneurship education has an important role throughout all education level, especially in the college , which its purpose to create a young generation of entrepreneur in the future.The purpose of this study were to analyze the influence of Entrepreneurship Education on Entrepreneurial Intention, the influence of Entrepreneurship Education on Entrepreneurial Motivation, and the influence of Entrepreneurial Intention toward Entrepreneurial Motivation. This study also investigates the mediating role of Entrepreneurial Motivation, related to entrepreneurship education and entrepreneurial intentions.The data analysis technique of this research was SEM, using smart software PLS (Partial Least Square). This study conducted on 150 private university students in Surabaya. The sampling method used in this research was non probability sampling with consecutive sampling method. The results showed that entrepreneurship education significantly influenced entrepreneurial intention with T-Statistic 2,020602, while entrepreneurship education had significant influence on entrepreneurial motivation with T-statistic 3,972756. The other results showed that entrepreneurial motivation had significant influence on entrepreneurial intention with T-statistic 3,651692. The results of the study showed that entrepreneurial motivation was not able to mediate the influence of entrepreneurship education on entrepreneurial intention.